Eduard von Lannoy - Suppan, Wolfgang (Traditiones (Ljubljana), 1999)
The author writes about several interesting details from the life and work of Austrian composer and conductor Eduard von Lannoy (1787-1853). In 1808 Lannoy's father purchased Viltus near Maribor. Although Lannoy worked in Graz and in Vienna, he was often spending the summer months in this castle
Keywords: Lannoy, Eduard von, 1787-1853; avstrijski skladatelji; folk music; ljudska glasba